Digital Marketing Strategy in the Development of Trap Sewu Waterfall Tourism in Bodang Village, Lumajang - Ramadhan, Ahmad Dimas; Asrohah, Hanun (Universitas Ibn Khaldun, 2025)
Trap Sewu Waterfall, which is located in Bodang Village, even though it has stunning natural beauty and high tourism potential, this waterfall is still little known by the wider community. This is caused by the lack of promotion and planned management. So Trap Sewu Waterfall, which is located in Bodang Village, Lumajang, requires an appropriate marketing strategy in the process of developing it as a tourist village. This research aims to determine marketing strategies in developing Trap Sewu Waterfall tourism in Bodang Village, Lumajang. The type of research used is Asset Based Communities Development (ABCD). The research results concluded that the digital marketing strategy carried out using digital media such as websites, Instagram and TV showed positive developments and succeeded in attracting the interest of visitors from various regions. Among them are: Increased traffic to the website, interaction and engagement on Instagram, increased coverage on television, increased tourist visits, and influencer engagement.